Extractive Industries in Forest Landscapes : Options for Synergy with REDD+ and Development of Standards in the Democratic Republic of Congo - Hund, Kirsten (Elsevier, 2018)
Mining and on-shore oil and gas extraction are a major driver of deforestation in tropical forests and account for an estimated 7% of total forest loss in Africa, Latin America and Asia (Hosonuma et al., 2012). At local levels, extractive industries can be a major cause of forest loss, as observed in parts of Papua New Guinea, India's Madhya Pradesh and Guyana (Areendran et al., 2013; Laurance et al., 2012; Lowe, 2014). With high global demand, economically valuable mineral resources in remote –often forested- areas, such as the Congo Basin, are more likely to become developed. New infrastructure corridors, associated with mineral exploitation and related hydropower needs, facilitate access to previously inaccessible tropical forest areas and accelerate development and forest clearing in developing regions (Edwards et al., 2014; Weng et al., 2013). Deforestation and degradation of tropical forests contribute an estimated 14–21% of global emissions (ISU, 2015). Mitigation of impacts on forests and reduction of related emissions is the main aim of policies on Reduction of Emissions from Deforestation and forest Degradation and improving carbon stocks (REDD+). Even though most mineral rich countries that are presently developing their REDD+ strategies have identified the extractive sector as a driver of deforestation, it is often not considered in related policies and actions. This paper explores options for extractives industries to contribute to REDD+ objectives, using insights gained from developing REDD+ Standards for extractives in the Democratic Republic of Congo. As mining is more prevalent in forest areas than oil and gas extraction, this paper focuses mainly on mining with the understanding that the underlying principles apply to the entire on-shore extractives industries.